LIPODERMATOSCLEROSIS AS A VARIANT OF LOBULAR PANNICULITIS: COURSE AND OUTCOMES - N. M. Savushkina; O. N. Egorova; S. I. Glukhova; S. G. Radenska-Lopovok; B. S. Belov (Современная ревматология)
Objective: to study the course and outcomes of lipodermatosclerosis (LDS) as a variant of lobular panniculitis.Patients and methods. Examinations were made in 38 patients (37 women and one man) aged 54±13 years who had been diagnosed with LDS lasting 2 weeks to 20 years and followed up at the V.A. Nasonova Research Institute of Rheumatology in 2009–2016. In addition to general clinical examination, the patients underwent immunological studies and lower extremity venous Doppler ultrasonography (DUSG). Outcomes were assessed as a significant improvement (complete regression of indurations), an improvement (regression of indurations was achieved, but there was one recurrence of LDS in the follow-up period), a slight improvement (regression of indurations was achieved, but there was more than one recurrence of LDS, which needed to change treatment policy), no effect of the therapy (no regression of indurations was achieved), and deterioration of health.Results. The 38 patients with LDS were noted to have subcutaneous fat inflammation in the leg (100%) and asymmetric inflammation (55%) on its medial surface (92%). If the body mass index (BMI) was normal, LDS regressed more rapidly (p=0.04). During the entire follow-up period, 16 (42%) patients were observed to have recurrent LDS; the median time to recurrence was 3 [1; 6] months. The development of a recurrence was associated with node merging into conglomerates [odds ratio (OR), 4.33; 95% confidence interval (CI), 1.05–17.8; p=0.037] and with the use of hydroxychloroquine (HCQ) agents at a dose <400 mg/day (OR, 5.25; 95% CI, 1.26–21.96; p=0.019). Regression of indurations was achieved in 39.5% of cases, the likelihood of its development was higher when the duration of LDS was ≤3 months before therapy initiation (OR, 14.67; 95% CI, 1.5–139.8; p=0.006) and in the absence of perforating vein valve incompetence, as evidenced by DUSG (OR, 4.1; 95% CI, 1.0–17.0; p=0.045).Conclusion. In the study group, LDS was more common in middle-aged women with increased BMI and chronic venous insufficiency. The elevated clinical and laboratory parameters of inflammatory activity were not typical of LDS. Higher BMI values contributed to a longer regression of indurations. Recurrences were more frequently observed after stress and due to non-compliance with prescribed therapy. Node merging into conglomerates and use of HCQ< 400 mg/day for ≥6 months after therapy initiation are risk factors of recurrent LDS. The likelihood of regression of indurations was higher in patients, in whom the duration of the underlying disease was ≤3 months before therapy initiation and perforator vein valve incompetence was absent, as evidenced by DUSC.